2005
DOI: 10.1055/s-2005-837464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Active Recovery from Supramaximal Exercise on Blood Lactate Disappearance in Trained and Untrained Man

Abstract: The purpose of this study was to determine the effect of different modalities of individualized active recovery on blood lactate disappearance after supramaximal exercise in subjects with different levels of aerobic fitness. Fourteen healthy subjects (7 trained and 7 untrained subjects mean age 20 +/- 1.5 and 19.5 +/- 1.5, respectively) participated in this study. They performed three supramaximal intermittent exercises at 60 % of the time to exhaustion at 120 % of the maximum aerobic power (MAP) with 5-min re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
5
13
0
1
Order By: Relevance
“…In accordance with the literature, the supramaximal exercise performed with normal frequency breathing (i. e., 1 breath every 4 strokes) induced a significant increase in heart rate and blood lactate in all subjects [9,14]. In parallel, it is interesting to note that the 50-m performed at maximal speed also induced, with normal frequency breathing, a significant decrease in arterial oxygen saturation in the whole population.…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with the literature, the supramaximal exercise performed with normal frequency breathing (i. e., 1 breath every 4 strokes) induced a significant increase in heart rate and blood lactate in all subjects [9,14]. In parallel, it is interesting to note that the 50-m performed at maximal speed also induced, with normal frequency breathing, a significant decrease in arterial oxygen saturation in the whole population.…”
Section: Discussionsupporting
confidence: 88%
“…These results are in line with previous studies that suggested that blood lactate recovery is faster in trained than untrained individuals during active recovery (Gmada et al, 2005), and that lactate recovery at a relative exercise intensity, expressed as a percentage of V O 2max , improves with increased aerobic power (Evans & Cureton, 1983). Further support for the role of V O 2max in lactate recovery comes from trained individuals who, compared with untrained participants, are able to remove lactate at higher exercise intensities (Davies et al, 1970;Dodd et al, 1984;Hermansen & Stensvold, 1972;Weltman et al, 1979).…”
Section: Lactate Recoverysupporting
confidence: 92%
“…Further, the Δ of whole blood LA showed no difference between both groups. This was also observed by Gmada et al who observed that whole blood LA peak values measured after different test modes did not differ between an aerobically trained and a untrained group (Gmada et al, 2005).…”
Section: Discussionsupporting
confidence: 82%